A multiple-case study examining elementary principals in high-poverty schools with teachers integrating new literacies - Stegman, Bridget (Kansas State University, 2014)
Today, students enter school with a variety of knowledge about technology. They are accustomed to using the Internet, cell phones, instant messaging, social networking, but that does not mean they have a deep understanding of the reading skills necessary to be successful at online reading (Leu et al., 2013). Reading on the Internet requires critical literacy skills and requires a different set of reading comprehension skills when compared to traditional print (Coiro & Dobler, 2007; Eaglerton & Dobler, 2007; Henry, 2006; Karchmer-Klein & Shinas, 2012; Leu et al., 2008; Leu et al., 2013). The purpose of this study was to gain insight into the knowledge, dispositions, and actions of principals perceived to be most meaningful by both the principals themselves and the teachers under their supervision in high-poverty schools with classroom teachers integrating new literacies. This study also examined the dimensions of instructional leadership (Hallinger & Murphy, 1985) and how these dimensions intersect with knowledge, dispositions, and actions of principals. Using a qualitative design, specifically a multiple-case study, the researcher interviewed teachers and principals at four, high-poverty elementary schools to gain insight into the principals’ role in the integration of new literacies. This study provides a deeper understanding of the many components involved in the leadership of a high-poverty school with classroom teachers integrating new literacies. The findings of this study include that the principals were literacy leaders. They were knowledgeable about the curriculum; ensured teachers had the appropriate resources to integrate new literacies (Internet, iPads, laptops, and tablets); and had high expectations for teachers in terms of technology integration. The principals created equitable opportunities for all students to participate in the integration of technology and literacy. Finally, the principals in this study created a culture of trust and professional growth for teachers.
Keywords: High-poverty; New literacies; Technology Integration; Principal; Case study; Educational leadership (0449); Education, Technology (0710); Elementary Education (0524)